Risk factors for postoperative recurrence of cesarean scar endometriosisAJOG Global Reports at a Glance - Qiyu Zhong, MD; Shuhang Qin, MD; Huiling Lai, MD; Shuzhong Yao, MD; Shuqin Chen, MD (Elsevier, 2024)
BACKGROUND: The increasing global prevalence of cesarean scar endometriosis necessitates a thorough understanding of the risk factors for postoperative recurrence, as this is crucial for developing preventive strategies and informed decision-making. OBJECTIVE: To obtain insight into the clinical risk factors for postoperative recurrence of cesarean scar endometriosis following open lesion resection. STUDY DESIGN: The cohort for this study comprised 272 women, including 26 patients with postoperative recurrence and 246 without recurrence. Various parameters, including baseline characteristics, preoperative, intraoperative, and postoperative conditions, and follow-up information, were analyzed. A comparison of these parameters was made between patients with and without postoperative recurrence. Time-to-recurrence analyses were conducted using Cox's univariate and multivariate proportional hazard analyses, the Kaplan-Meier method, and the log-rank test. RESULTS: The results revealed significant differences between patients with and without postoperative recurrence in terms of visual analog scale for abdominal pain (P=.008), method of surgery (P<.001), and incision length (P=.002). The Cox proportional hazard model identified the visual analog scale for abdominal pain ≥4 as a significant risk factor for postoperative recurrence (hazard ratio, 3.72 [95% confidence interval, 1.65-8.43]; P=.002). In addition, patients who received removal of scar, excision of mass, and exploration underneath the scar (named as integrated excision) had a lower risk of recurrence than those who received local excision of mass (hazard ratio, 0.14 [95% confidence interval, 0.04-0.48]; P=.002). Furthermore, older patients (aged ≥35 years) were found to have a lower risk of postoperative recurrence than those <35 years (hazard ratio, 0.35 [95% confidence interval, 0.12-1.04]; P=.058). In addition, the depth of involvement was identified as a meaningful factor in postoperative recurrence for patients with local excision of mass, as determined by the log-rank test (P=.018). CONCLUSION: The study highlights that the visual analog scale for abdominal pain ≥4 is a risk factor for the recurrence of cesarean scar endometriosis after open lesion resection. Furthermore, the surgical method of integrated excision was identified as a protective factor.